Oxidative stress-related risk of the multiple sclerosis development - Vasic, Marija; Topic, Aleksandra; Markovic, Bojan; Milinkovic, Neda; Dincic, Evica (Journal of Medical Biochemistry, 2022)
Background: Multiple sclerosis (MS) is characterized by inflammation, demyelination and axonal degeneration. Oxidative stress (OS) plays a significant role in the pathogenesis of the disease. The aim of the study was to examine the association between OS and smoking on the MS development.Methods: The study included 175 patients with relapsing-remitting multiple sclerosis (RRMS) (76 males, 99 females) and 254 healthy subjects (81 males and 173 females). Oxidative stress biomarkers in serum, Total Antioxidant Status (TAS) and Total Oxidative Status (TOS) were determined spectrophotometrically. Oxidative Stress Index (OSI) was calculated as the ratio of TOS and TAS. Urinary 8-oxo-7,8-dihydro-2´-deoxyguanosine were determined by HPLC-MS/MS and expressed as 8-oxodG/creatinine.Results: In females with RRMS were higher TOS, OSI and 8-oxodG/creatinine than in females in control group. The group of males with RRMS had lower level of TAS than the males in control group. Higher levels of 8-oxodG/creatinine was obtained in active, passive and former smokers with RRMS than in control group with the same exposition to tobacco smoke. Independent predictors of MS are passive smoking, increased OSI and increased levels of urinary 8-oxodG/creatinine.Conclusion: Our results demonstrate that the OS parameters should be included in the assessment of the risk for MS development. Due to the more sensitivity to oxidative stress, females may be at higher risk of MS development. This data indicates the importance of introducing the antioxidant therapy as a complementary treatment in patients with RRMS.
Keywords: multiple sclerosis, oxidative stress, oxidative stress index, 8-oxo-7,8-dihydro-2´-deoxyguanosine, total antioxidant status, total oxidative status